(untitled) (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2025)
Selection committee at Jetis Village Sukoharjo Regency, Indonesia had difficulty to assign FHP assistance recipients priority. This is a problem must be resolved so that selection committee can be helped to determine which candidates are entitled to receive. This research is to develop a system using Rank Order Centroid (ROC) and Technique For Order Preference By Similarity to Ideal Solution (TOPSIS) methods and measure accuracy level of two methods used. Data used is 150 on potential 2024 FHP assistance recipients obtained from Jetis. From 150 real data in 2024, there were 71 people receiving FHP assistance, while a system developed in this research is produced 62 recipients. ROC method is used to specify each criterion importance level and TOPSIS method to process data which ultimately results in a potential ranking aid recipients. From comparison of original data and research results, there were 121 data had same system output as original data. From an accuracy rate of 81%, ROC and TOPSIS methods show the potential to increase accuracy and fairness in determining priority for candidates who are entitled to receive FHP assistance.